Literature Review: Hubungan Sarana Sanitasi Lingkungan dan Personal Hygiene Ibu dengan Kejadian Diare pada Balita: Literature Review: Relationship of Mother’s Environmental Sanitation and Personal Hygiene Facilities with the Event of Diarrhea in Toodlers - Made Ayu Suryati; Dewi Klarita Furtuna; Arieta Rachmawati Kawengian (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Background: Diarrhea is still a major health problem in developing countries and one of them is Indonesia. Having weak antibodies causes toddlers to be susceptible to viral diarrhea. Diarrhea is a contagious disease characterized by symptoms such as: increased frequency of defecation that can occur more than 3 times a day, then there is also a change in the shape or consistency of the stool which turns soft or even liquid, and this can cause vomiting that can make the sufferer have lack of body fluids (dehydration) and if it is not immediately to get help it can cause the sufferer to death. Objective: To determine the relationship between environmental sanitation facilities and mothers’ personal hygiene with cases of diarrhea in toddlers. Methods: The research design used in this study is in the form of a systematic review using secondary data. The data was searched using the PRISMA method, while the data synthesis is using the SPIDER approach. Results: There were 23 journals, the 23 journals consisted of 15 national journals and 8 international journals that were reviewed. Conclusion: There is a relationship between environmental sanitation facilities and mothers' personal hygiene with diarrhea incidence in toddlers. The importance of having sanitation facilities that meet the health requirements and the importance of conducting CTPS to reduce the risk of diarrhea in toddlers.